Evaluation of Blood-Based Antibody Rapid Testing for HIV Early Therapy: A Meta-Analysis of the Evidence - Huang, Xiaojie; Liu, Xinchao; Chen, Jieqing; Bao, Yugang; Hou, Jianhua; Lu, Xiaofan; Xia, Wei; Xia, Huan; Song, Aixin; Liu, Zhiying; Su, Bin; Chen, Hui; et al. (Frontiers in Immunology, 2018)
Abstract Background: Western Blot (WB) assay is considered the gold standard test for HIV infection confirmation. However, it requires technical expertise and is quite time-consuming. WHO recommends blood-based rapid diagnosis to achieve same-day test and treatment. However, this rapid testing strategy has not been promoted worldwide due to inadequate research evaluating the effectiveness of rapid tests as an alternative confirmatory HIV test for WB. This study aims to compare the diagnostic performance of rapid HIV tests compared with WB. Methods: PubMed and Web of Science were searched for publications on rapid HIV tests using blood specimen. A meta-analysis was performed to quantitatively evaluate the diagnostic performance of rapid HIV tests compared with the WB assay in terms of pooled sensitivity, specificity, area under summary receiver operating characteristic (SROC) curve and diagnostic odds ratio (DOR) Results: Twenty articles involving 27343 fresh specimens for rapid HIV tests were included in the meta-analysis. Regarding Capillus HIV-1/HIV-2,the pooled sensitivity, specificity, area under SROC curve and DOR derived from six studieswere 0.999 (95% CI, 0.956-1.000), 0.999 (95% CI, 0.991-1.00), 1.00 (95% CI, 0.99-1.00) and 1.0106 (95% CI, 2.6104- 3.9107) compared with the WB assay, respectively. With respect to Determine HIV-1/2, the pooled sensitivity, specificity area under SROC and DOR derived from eight studies were 1.00 (95% CI, 0.789-1.000), 0.992 (95% CI, 0.985-0.996), 1.00 (95% CI, 0.99-1.00) and 1.8106 (95% CI 406.049-7.8109) compared with the WB assay, respectively. Regarding two-step serial rapid tests, the pooled sensitivity, specificity area under SROC and DOR derived from eight studies were 0.998 (95% CI, 0.991-1.000), 0.998 (95% CI, 0.994-0.999) and 1.00 (95% CI 0.99-1.00) compared with the WB assay, respectively. Conclusion: Our meta-analysis results may provide evidenced-based support for substituting rapid test for WB. Blood-based rapid HIV tests have comparable sensitivity and specificity to WB for HIV early therapy.